Expression of PTX3, HAS2 AND TNFAIP6 genes in relation to real-time proliferation of porcine endometrial luminal epithelial cells in primary cultivation model - Wojtanowicz-Markiewicz, K; Kocherova, I; Jeseta, M; Piotrowska-Kempisty, H; Brüssow, K P; Skowroński, M T; Bruska, M; Bukowska, D; Nowicki, M; Kempisty, B; Antosik, P (Journal of biological regulators and homeostatic agents, 2019)
Endometrial cells undergo very specific changes associated with reproductive processes. Cells prepare for embryo development by increasing their volume. Then, if fertilization fails, endometrial cells are liable for apoptosis, preparing new cells that are ready for subsequent processes related to the possibility of embryo implantation and the development of pregnancy. PTX3 and TNFAIP6 are absent or reduced in cultured COCs, resulting in a functional change in COC in vitro. In this work, we want to check how PTX3, HAS2 and TNFAIP6 behave in luminal epithelium primary cell culture. Cells obtained during slaughter from porcine specimens were cultured primarily in vitro for 7 days. Their proliferation patterns were then analysed using RTCA, with the expression of genes of interest evaluated with the use of immunofluorescence and RT-qPCR. The results of these changes in the expression of the genes of interest were analysed on each of the seven days of the porcine luminal primary cell culture. Our study showed the increased level of PTX3, HAS2 and TN¬FAIP6 expression at the same hours of primary culture. Rt-qPCR showed a higher level of expression of the PTX3 gene in the first 72 h, at the end of the lag phase (in the phase of stasis in which the cells adapt to the new environment and often die). In contrast, TNFAIP6 expression increases about 96 hours when the cells are in the full log phase (logarithmic phase growth) and continue this trend in the plateau phase. We did not observe such drastic changes in the HAS2 expression pattern, which leads us to hypothesize that PTX3 and TNFAIP6 are designed to maintain a constant level of HAS2 in the cell throughout its lifetime. The obtained results could become a point of reference for further in vivo and clinical research.
Keywords: endometrium; Endometrium; prasata; Cell Proliferation; Hyaluronan Synthases; Female; Epithelial Cells; pig; C-reaktivní protein; genes expression; primary culture; Serum Amyloid P-Component; Swine; epitelové buňky; proliferace buněk; hyaluronansynthasy; Primary Cell Culture; luminal epithelial cells; primární buněčná kultura; zvířata; ženské pohlaví; Animals; sérový amyloidový protein; C-Reactive Protein; molekuly buněčné adheze; Cell Adhesion Molecules